Integrated management of Meloidogyne graminicola under basmati rice (Oryza sativa)-wheat (Triticum aestivum) cropping system - SINGH, SATYENDRA; TANWAR, R K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2021)
Survey conducted in and around village Bambawad, Gautam Budh Nagar, UP, for nematode population density infested basmati rice and wheat during 2015 indicated low population of rice root-knot nematode, Meloidogyne graminicola in IPM adopted fields compared with farmer’s practices (FP). With this view, the study was carried out to manage M. graminicola under basmati rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system taking advantage of IPM technology developed and validated by ICAR-NCIPM for basmati rice during 2016-19 with some modifications such as soil solarisation, bio-agents etc. Soil solarisation of nursery beds reduced population density of test nematode up to 93.4%, whereas an increase of up to 46% in FP compared to initial population. Analysis of root and soil samples of both rice and wheat crop from IPM fields showed either no visible galling or only 1-3% root galling severity (RGS) and significantly (P>0.05) low population density compared to FP. In addition, the population of beneficial soil nematodes (BSN) remained high and significantly (P>0.05) higher in IPM as compared to FP with student’s t-test. Role of BSN in increasing the nutrient availability through organic matter decomposition has already been established. It is evident from the study that IPM technology might have played important role in antagonising the M. graminicola and increased the density of BSN. This technologycould be a safe and eco-friendly alternative to manage M. graminicola below ETL. Also, it has helped in sustaining IPM by the way of saving on the cost of application of pesticides and enhancing the benefit-cost ratio.